Implementing Quizizz in Islamic Education: Enhancing Learning Engagement in Modern Classrooms - Sundari, Susan; Nugraha, Mulyawan Safwandy; Dedih, Ujang (Jurnal Inovasi Pendidikan Agama Islam (JIPAI), 2024)
The formation of student character is a key objective of Islamic Religious Education (PAI). To sustain students' interest and motivation in learning, effective and engaging assessment tools are essential. Quizizz, an interactive online platform, offers innovative solutions to achieve this. The digital era has significantly impacted education, with technology enhancing its quality. Quizizz is one of the popular tools in this regard. This study aimed to evaluate the implementation of Quizizz in PAI at SMP Sains Alquran Baitul Arqam. Using the Research and Development (R&D) approach, the study developed and assessed Quizizz’s effectiveness. The findings revealed Quizizz to be efficient, impactful, and conducive to interactive learning. Validation results supported its reliability, with material experts rating it 98.1%, media experts 85%, teachers 97.5%, and students 90%. These results affirm that Quizizz is a practical and effective tool for enhancing educational outcomes in PAI.